Crafting a next-generation device using iron oxide thin film: a review - Amrillah, Tahta; Che Abdullah, Che Azurahanim; Sari, Dita Puspita; Mumtazah, Zuhra; Fayza Putri Adila; Astuti, Fahmi (American Chemical Society, 2021)
Despite extensive research into novel materials, iron oxides remain fascinating and attract considerable attention because of their versatility, stability, ease of fabrication, low cost, natural abundance, and environmental friendliness. Because of their wealth of magnetic, optical, and electrical properties, iron oxides are particularly multifunctional materials that can be integrated into various devices. In this article, we will discuss the applications of iron oxide thin films in electronics (spintronics devices), energy (batteries and solar cells or photovoltaics), and sensors (gas, humidity, strain, biosensors, and so on). We begin with the most recent forms and fabrication methods for iron oxide thin film, as well as a fundamental understanding of the material. Additionally, the application constraints of these devices are discussed, and the challenges, solutions, and prospects for electronic devices based on iron oxide are outlined.